THE IMPLEMENTATION OF PROJECT-BASED AND CONTEXTUAL TEACHING METHODS TO ENHANCE ENGLISH SPEAKING SKILLS: A QUALITATIVE STUDY AT STIS DARUL FALAH - Abrar (Kurikula : Jurnal Pendidikan, 2025)
Teaching methods play a vital role in enhancing students' learning experiences, with each method offering unique strengths and challenges. This study explores the integration of two widely used pedagogical approaches—Project-Based Learning (PBL) and Contextual Teaching and Learning (CTL)—to improve English speaking skills at STIS Darul Falah. Employing a qualitative research design, the study investigates the implementation of these methods in the classroom, challenges encountered by both lecturers and students, and strategies for optimizing their integration to achieve more effective learning outcomes. The data was collected through a combination of classroom observations, semi-structured interviews with both students and lecturers, and document analysis of lesson plans and student work. The findings indicate that the combination of PBL and CTL significantly boosts students' confidence, vocabulary, fluency, and critical thinking, leading to an overall improvement in speaking skills. However, challenges such as time constraints, varying proficiency levels, and technological limitations were identified. To enhance the integration of PBL and CTL, the study finds several strategies, one of which is providing better scaffolding for students with diverse proficiency levels, improving access to online learning tools, collaborative platforms, and multimedia resources, and utilizing technology to design engaging and relevant projects. Additionally, continuous professional development for lecturers is crucial for sustaining the success of these methods. The core of the integration of PBL and CTL is to create a learning environment that is more interactive, contextual, and oriented towards the development of practical skills that can help students become better prepared to face real-world challenges.